The Nominal Group Technique as a tool to select items that measure the level of digital skills in postgraduate students - Rodríguez Pavón, Pedro René; Morales Salas, Rubí Estela; Infante-Moro, Alfonso; Infante-Moro, Juan C. (IJERI: International Journal of Educational Research and Innovation, 2024)
Digital competence has become crucial in the digital era and understanding the digital skills level of postgraduate students is essential to adapt educational programs and develop effective teaching and learning strategies. The objective of this research was to select the items of a questionnaire to assess the level of digital skills in postgraduate students in a specific situation, using the Nominal Group Technique (NGT). Study participants were selected for their experience and knowledge in the field of digital skills. A structured discussion was held in which the experts identified and discussed the key dimensions and components of digital competences relevant to postgraduate students, and the most representative items that would measure the level of digital skills in students were prioritized and selected. The outcomes provided a set of validated and reliable items included in a questionnaire that is tailored to previously identified digital skills. This questionnaire can effectively assess the level of digital skills in postgraduate students in a specific context, the outcomes of which help inform educational policies and strategies that improve digital skills training in reference students.